When tradition turns into innovation : how firms can create and appropriate value through tradition - Messeni Petruzzelli, Antonio; Albino, Vito. (Oxford, UK : Chandos Pub., 2012)
Starting from the increasing difficulties firms face to create new value for customers and achieve competitive advantage, this book proposes an innovative strategy to sustain innovation at the product level, based on the notion of tradition. Specifically, the authors argue that firms may successfully innovate, exploiting the whole set of competencies, knowledge, values and culture that characterize a specific firm, territory, and/or age. Analyzing several international case studies, this book clearly shows how tradition may be effectively used, allowing companies to create successful new products and how to profit from them. The book tackles the main issues and problems of a tradition-based innovation approach, tracing the patterns of how old and new knowledge can be combined. Proposes a new strategic model for promoting and sustaining innovation at product levelMerges a theoretical perspective with actual casesDevelops a set of implications that allows managers and practitioners to implement an alternative approach to innovation.
Includes bibliographical references (pages 127-132) and index.
Keywords: 2000-2099; Technological innovations -- Economic aspects; Knowledge management; Intellectual property -- Valuation; Financial crises -- History -- 21st century; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Financial crises; Intellectual property -- Valuation; Knowledge management; Technological innovations -- Economic aspects; Produktinnovation; Know-how; Tradition; Unternehmenskultur